Past, Present, and Future of Technological Business Development: A Bibliometric Study - Shobeiri, Seyyed Amir Hossein (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: Business development is a capability consisting of practices and skills involved in identifying opportunities, directing, and employing resources to expand a company's value-creating activities in areas of technology or markets that are relatively new to the company, thus enabling growth. In recent years, researchers have shown an increased interest in the area of technological business development, leading to a considerable accumulation of knowledge in this field.Methodology: Accordingly, the current research utilized a systematic review approach, employing the PRISMA protocol for document screening. A bibliometric review of 205 studies, from 1984 to the present, was conducted using data analysis software such as VOSviewer and R. This included performance analyses such as the analysis of the most influential journals and authors in the field of technological business development, and network analyses including co-citation of authors, co-citation of countries, and co-occurrence of terms. The findings of this research can be beneficial for researchers and policymakers in the field of technological business development.Findings: The analyses indicate that the leading author in the field of technological business development, who has the most global citations in this area, is Keil. His article, titled "The impact of governance methods and the articulation of external business development activities on innovative performance," was published in 2008. Indeed, his paper is the most important and most cited in this field. In terms of the most influential journal, the analyses show that the journal Technological Forecasting and Social Change is the most influential in the field of technological business development. As for the most influential countries, Finland has the highest number of citations in the field of technological business development, followed by Poland, China, Korea, the Netherlands, the United Kingdom, Germany, India, the United States, and Romania.Conclusion: The results of the network analysis in this study clarified that based on the co-citation patterns of researchers, a cluster core author named Theis has the most co-citations among various authors. Additionally, the co-citation analysis of countries shows that there is established collaboration between Pakistan and Chile, Chile and China, Georgia and China, Pakistan and China, the United Kingdom and China, Macedonia and Croatia, North Macedonia and Croatia, the United Kingdom and Finland, France and India, as well as Italy and India. In the analysis of keyword co-occurrence, the results highlighted that the most frequent co-occurrences with the field of technological business development are terms such as technology, economy, strategic planning, research and development management, innovation, communities and institutions, product development, project management, small businesses, and new business development.